Relationship of virtue with happiness according Farabi (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Happiness according to the Farabi is ultimate goal of human life and it is the purpose he aimed to achieve from his intellectual project.He saw that the real happiness is achieved in the virtuous society that led by wise presidentAccording to the Farabi achieving virtues help the proses of organization of the city and the distinction between Good and evil in order to reach their members to ultimate perfection of human life.